V.I.T.A.M. in COVID 19: A Systematic Approach to a Global Pandemic. Issue 15 (September 2021) - Yarrarapu, Siva Naga S.; Bansal, Pankaj; Abia-Trujillo, David; Cusick, Austin; Melody, Megan; Moktan, Varun; Rivero, Andrea; Brigham, Tara J.; Libertin, Claudia; Brumble, Lisa; O'Brien, Jennifer J.; Lee, Augustine; et al.
Introduction: In the unprecedented era of COVID-19, ongoing research and evolution of evidence has led to ever-changing guidelines for clinical monitoring and therapeutic options. Formulating treatment protocols requires the understanding and application of the evolving research. Objective: The primary objective of this study is to present a systematic evidence-based approach to synthesize the necessary data in order to optimize the management of COVID-19. Methods: At Mayo Clinic Florida, we developed a multidisciplinary centralized COVID Treatment Review Panel (TRP) of expert pulmonologists, intensivists, infectious disease specialists, anesthesiologists, hematologists, rheumatologists, and hospitalists that in real-time reviews the latest evidence in peer-reviewed journals, the available clinical trials, and help guide the rapid application of therapeutics or interventions to the patient and the bedside provider. Results/Conclusions: The multi-disciplinary team approach of synthesizing clinical data and coordinating care is effective in responding to rapidly evolving and changing evidence. Systematic data collection and evidence-based treatment algorithms enable physicians to rapidly translate the current literature to clinical practice, and improve care and outcomes of patients.